Effects of pH, temperature, ionic strength and organic matter on triclocarban solubility - Ivan, Georgeta Ramona; Ion, Ion; Capra, Luiza; Ion, Alina Catrinel (Journal of Environmental Engineering and Landscape Management, 2021)
The solubility of triclocarban in ultrapure water and in several natural aqueous solutions is influenced by several environmental factors. In this study the variation of temperature, pH, ionic strength and concentration of the organic matter over the solubility of triclocarban was analysed. The results show that the solubility of triclocarban increases by increasing the contact time, longer than the time of equilibrium and the temperature. It is less influenced by the variations of pH and strongly influenced by the variation of ionic strength and by the natural organic matter into the studied aqueous matrices.